The Sexual Development, Sexual Health, Sexual Experiences, and Sexual Knowledge of Forensic Mental Health Patients: A Research Design and Methodology Protocol - Brand, Elnike; Ratsch, Angela; Heffernan, Edward (Frontiers in Psychiatry, 2021)
Introduction There is substantial evidence that mental illness can have significant impacts on general development, knowledge acquisition, and quality of life including sexual function. However, whilst the sexual development, sexual health, sexual experiences and sexual knowledge of the broader Australian community and the Australian prisoner population have been well-described, these concepts have been less explored in people with a mental illness. In particular, there is an absence of research around these topics involving people who are subject to a treatment order under the relevant jurisdictional Mental Health Act (aka a Forensic Order). Methods and analysis People currently under the treatment requirements of a Queensland Forensic Order will be invited to participate in this descriptive, mixed-method cross-sectional study. The study will be conducted in three phases. The first two phases will involve 50 participants (100 face-to-face quantitative interviews) with the aim of mapping sexual development, sexual health, sexual experiences and sexual knowledge. The third phase will involve qualitative semi-structured interviews with a purposely enrolled, informant-rich cohort identified through the quantitative surveys until saturation is reached. Quantitative data will be analyzed using descriptive and comparative statistics. Qualitative data will be analyzed by content analysis of the major themes.